Entrepreneurial Orientation and Innovation Performance in Family-Owned Turkish Enterprises - Özturan, Nadzeya; Ören, Ali Şahin; Çakar , Sevgin Şahin (PT. Sangadji Media Publishing, 2025)
This study explores the relationship between entrepreneurial orientation (EO) and innovation performance in family-owned enterprises in Turkey, with a focus on the role of family dynamics. Using qualitative methods, the research examines how EO, as a legacy mindset passed down through generations, influences innovation strategies within these firms. The findings reveal that while EO provides continuity and a sense of stability, it can also hinder innovation when family values and traditions conflict with the need to adapt to rapidly changing market conditions. Furthermore, the study identifies the tension between maintaining traditional practices and embracing innovative changes, emphasizing that innovation in family firms is a process of negotiation between these two forces. The research highlights how family dynamics, such as emotional ties and generational differences, act as both enablers and constraints of innovation. In particular, the dominance of family leaders and the power structures within the family can limit the participation of younger generations in innovation decision-making. This study contributes to the literature by providing insights into how family businesses balance tradition and innovation, offering practical implications for improving innovation performance while preserving family values. The novelty of this research lies in its focus on the intersection of EO, innovation, and family dynamics in family-owned businesses, particularly within the context of Turkey, a region underexplored in this field.